Master curves for the sulphur assisted crosslinking reaction of natural rubber in the presence of nano- and nano-structured sp2 carbon allotropes - S. Musto; V. Barbera; V. Cipolletti; A. Citterio; M. Galimberti (eXPRESS Polymer Letters, 2017)
In this paper, master curves are reported for the crosslinking of a diene rubber with a sulphur based system in the presence of either nano- or nano-structured carbon allotropes, such as carbon nanotubes (CNT), a nanosized graphite with high surface area (HSAG) and carbon black (CB). Poly(1,4-cis-isoprene) from Hevea Brasiliensis was the diene rubber and crosslinking was performed in temperatures ranging from 151 to 180 °C, with carbon allotropes below and above their percolation threshold. Such carbon allotropes were characterized by different aspect ratio, surface area and pH. However, in the crosslinking reaction, they revealed common behaviour. In fact, the specific interfacial area could be used to correlate crosslinking parameters, such as induction time (ts1) and activation energy (Ea) calculated by applying the autocatalytic model. Monotonous decrease of ts1 and increase of Ea were observed, with points lying on master curves, regardless of the nature of the carbon allotropes. Remarkable differences were however observed in the structure of the crosslinking network: when the carbon allotrope was above the percolation threshold much larger crosslinking density was obtained in the presence of CNT whereas composites based on HSAG became soluble in hydrocarbon solvent, after the reaction with a thiol. Proposed explanation of these results is based on the reactivity of carbon allotropes with sulphur and sulphur based compounds, demonstrated through the reaction of 1-dodecanethiol and sulphur with CNT and HSAG and with a model substrate such as anthracene.